New insights about phenotypic heterogeneity within Propionibacterium freudenreichii argue against its division into subspecies - de Freitas, Rosangela (Dairy Sci Technol, 2015)
Propionibacterium freudenreichii is widely used in Swiss-type cheese manufacture, where it contributes to flavour and eye development. It is currently divided into two subspecies, according to the phenotype for lactose fermentation and nitrate reduction (lac(+)/nit(−) and lac(−)/nit(+) for P. freudenreichii subsp. shermanii and subsp. freudenreichii, respectively). However, the existence of unclassifiable strains (lac(+)/nit(+) and lac(−)/nit(−)) has also been reported. The aim of this study was to revisit the relevance of the subdivision of P. freudenreichii into subspecies, by confirming the existence of unclassifiable strains. Relevant conditions to test the ability of P. freudenreichii for lactose fermentation and nitrate reduction were first determined, by using 10 sequenced strains, in which the presence or absence of the lactose and nitrate genomic islands were known. We also determined whether the subdivision based on lac/nit phenotype was related to other phenotypic properties of interest in cheese manufacture, in this case, the production of aroma compounds, analysed by gas chromatography-mass spectrometry, for a total of 28 strains. The results showed that a too short incubation time can lead to false negative for lactose fermentation and nitrate reduction. They confirmed the existence of four lac/nit phenotypes instead of the two expected, thus leading to 13 unclassifiable strains out of the 28 characterized (7 lac(+)/nit(+) and 6 lac(−)/nit(−)). The production of the 15 aroma compounds detected in all cultures varied more within a lac/nit phenotype (up to 20 times) than between them. Taken together, these results demonstrate that the division of P. freudenreichii into two subspecies does not appear to be relevant.